A Study on Factors Influencing the Choice of Investors towards Mutual Funds - Arora, Nittan; Chawla, Dr. Sonia (The journal of contemporary issues in business and government, 2021)
The study is based on a sample of 200 qualified respondents chosen using multistage random sampling to understand the influence of various factors on investment decision and choice of investment towards mutual funds. The article identifies association of attributes risk perception, investment pattern and risk taking ability with demographic factors. Study mainly focuses on the factors influencing the choice of investors towards mutual funds and the impact of demographic factors on risk perception, investment pattern and risk taking ability of mutual fund investors. 283 respondents contacted for getting 200 mutual funds investors. Chi-square & Henry Garret Rating techniques applied for analysis the data. Regular return on schemes has emerged to be the most important factor and less Procedure least important factor that affects the choice of the investors towards selecting mutual funds. Most of the demographic factors have no significant association with investment pattern, risk perception and risk taking ability.